Comparison between Shura and Democracy - Ahmed, Ibrahim Al-Amin (Journal of Islamic Sciences, 2018)
The aim of this research is a comparative study between Islamic Shura and Western Democracy, to identify the differences between the two terminologies in terms of definition and source, principles and the field of both, and their characteristics and how to set their councils and their mandates in each of them. So the study has included the definition of Shura linguistically and as terminology, legislatively and how to apply it. And the personnel who have the mandate (decision makers).This research also aim at studying Shura principles and its rules, the field of Shura, the objectives of it. Then this research set a definition for democracy linguistically and as terminology, and also mentioned a historical gesture of democracy and the types of it, the characteristics of democracy and the main differences between Shura and democracy and then the disadvantages of democracy. I reached a conclusion through this research that the differences are far between Shura and democracy.The most important of these differences is that democracy is man made in its core source and the Shura is a God order.This resulted in differences in terms of objectives, groups, constants and amendments and lastly the mandate.Democracy and Shura both work in accordance with ideological and belief systems which, are being there ,so democracy works in secularity and Shura works with Islamic belief, so it’s injustice to equalize between democracy and Shura. Democracy has its own disadvantages, Muslims have to go back considering Shura in their life matters without any kind of fabrications or amendments so as not to serve personal interests, and this is what we are hoping for.
Keywords: Shura; Democracy; Interests; Islam